A systematic evaluation on the impact of sample-related and environmental factors in the analytical performance of acoustic emission from laser-induced plasmas - Bosáková, Markéta; Purohit, Pablo; Álvarez-Llamas, César; Moros-Portolés, Javier; Novotný, Karel; Laserna-Vázquez, José Javier (Elsevier, 2022)
Acoustics recordings from laser-induced plasmas are becoming increasingly regarded as a complementary source of information from the inspected sample. The propagation of these waves is susceptible to be modified by the physicochemical traits of the sample, thus yielding specific details that can be used for sorting and identification of targets. Still, the relative fragility of the acoustic wave poses major challenges to the applicability of laser-induced acoustics. Echoes and reflections sourcing from intrasample parameters as well as from interactions of the acoustic wave with the surroundings of the inspected target can dilute the analytical information directly related to the object contained within the recordings. The present work aims to experimentally scrutinize the impact of different parameters internal and external to the sample into the final acoustic signal from laser-induced plasmas in order to accurately use this information source for characterization purposes. Variables inherent to the sample such as dimensions, porosity and absorption coefficient, which guides the laser-matter coupling process, have been, for the first time, systematically studied using ad-hoc solids to thoroughly isolate their influence on the signal. Moreover, modulation of soundwave induced by the surroundings of the probed target and the anisotropy of the acoustic signal because of the angle at which the plasma is formed, have been evaluated.
Keywords: Plasmas producidos por láser; Acoustics; Plasmas; Laser; Plasmaphony; Solids